Self–other overlap and interpersonal neural synchronization serially mediate the effect of behavioral synchronization on prosociality. Issue 2 (12th February 2020) - Feng, Xiaodan; Sun, Binghai; Chen, Chuansheng; Li, Weijian; Wang, Ying; Zhang, Wenhai; Xiao, Weilong; Shao, Yuting
Abstract: Behavioral synchronization has been found to facilitate social bonding and prosociality but the neural mechanisms underlying such effects are not well understood. In the current study, 60 dyads were hyperscanned using functional near-infrared spectroscopy while they performed either a synchronous key-pressing task or a control task. After the task, they were asked to perform the dictator game to assess their prosocial behavior. We also measured three potential mediating variables: self–other overlap, perceived similarity and interpersonal neural synchronization. Results showed that dyads in the synchronization group were higher in behavioral synchronization, interpersonal neural synchronization (INS) at the right dorsolateral prefrontal cortex, self–other overlap, perceived similarity and prosociality than those in the control group. INS was significantly associated with prosocial behaviors and self–other overlap. After testing four meditation models, we found that self–other overlap and INS played a serial mediation role in the effect of behavioral synchronization on prosociality. These results contribute to our understanding of the neural and cognitive mechanisms underlying the effect of behavioral synchronization on prosocial behavior.